Pelatihan Penghitungan Pemotongan Pph 21 Bagi Warga Rw 02 di Kelurahan Dukuh Setro, Kecamatan Tambak Sari, Surabaya - Hidayatul Khusnah; Mardiyah Anugraini; Mohamad Yusak Anshori; Firdeana Fitrotul Ula (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Most of the state revenue is from the tax sector. This is because until now state revenues from the tax sector are still a top priority for the success and launch of sustainable national development. To build a good economy, companies as tax cutters have a very big role for the government. Considering that currently there are not a few companies that carry out tax cuts that are not in accordance with the provisions of the applicable law. Therefore, for smooth tax cuts, good cooperation between the government and companies is needed. Employers are also obliged and responsible for calculating, withholding, paying, and reporting the amount of tax that must be withheld and paid on individual income in connection with a job, service, or activity carried out in accordance with the withholding tax system. There are still many companies that have not explained properly the PPh 21 tax to employees, so there are still many people who do not know and understand the calculation of personal tax deductions and usually only receive money that has been deducted from taxes. With this community service activity, training and assistance activities will be held regarding calculating the withholding of PPh 21 tax in the community. The targets who will be given training in this activity are residents of RW 02, Dukuh Setro Village, Tambak Sari District, Surabaya.